2008
DOI: 10.1126/science.1151086
|View full text |Cite
|
Sign up to set email alerts
|

Assembly Mechanism of the Contractile Ring for Cytokinesis by Fission Yeast

Abstract: Animals and fungi assemble a contractile ring of actin filaments and the motor protein myosin to separate into individual daughter cells during cytokinesis. We used fluorescence microscopy of live fission yeast cells to observe that membrane-bound nodes containing myosin were broadly distributed around the cell equator and assembled into a contractile ring through stochastic motions, after a meshwork of dynamic actin filaments appeared. Analysis of node motions and numerical simulations supported a mechanism w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
599
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(638 citation statements)
references
References 19 publications
33
599
0
6
Order By: Relevance
“…Later, cortical nodes coalesce during the 'lateral condensation' process to form a ring structure. 8,[12][13][14] Concomitantly, F-actin cables are formed in parallel in the cell centre and are packed as a ring. A homogeneous ring structure is achieved by the incorporation of the FER/CIP4 homology (FCH) domain protein Cdc15.…”
Section: Introductionmentioning
confidence: 99%
“…Later, cortical nodes coalesce during the 'lateral condensation' process to form a ring structure. 8,[12][13][14] Concomitantly, F-actin cables are formed in parallel in the cell centre and are packed as a ring. A homogeneous ring structure is achieved by the incorporation of the FER/CIP4 homology (FCH) domain protein Cdc15.…”
Section: Introductionmentioning
confidence: 99%
“…Two major models have been proposed. The Search, Capture, Pull, and Release (SCPR) n 772Rincon and Paoletti CYTOSKELETON model proposes that actin filaments nucleated by Cdc12 from each node search for nearby nodes, in which Myo2 captures actin filaments and produces the force necessary to pull nodes together, resulting in the condensation into a ring structure [Wu et al, 2006;Vavylonis et al, 2008;Ojkic et al, 2011]. The alternate Cdc12 Spot-Leading Cable model proposes that a major Cdc12 spot moves toward the cell middle and nucleates an actin leading cable beneath the plasma membrane and perpendicular to the long axis of the cell, which eventually gives rise to the contractile ring [Chang, 1999;Kamasaki et al, 2007].…”
mentioning
confidence: 99%
“…In the mature ring, the actin filaments average 600 nm in length and show interdigitation. Live-imaging studies with fluorescent proteins revealed that the contractile ring assembles from a series of cortical nodes that contain myosin motors and simultaneously nucleate actin assembly (Vavylonis et al 2008). These nodes assemble into rings by means of a pathway that will be discussed in detail below.…”
Section: Accessory Structures In Fission and Budding Yeastmentioning
confidence: 99%
“…These two types of nodes fuse in late G 2 in the cell center, and some type 1 node components dissipate from these hybrid, cytokinetic nodes during M phase ( . These nodes then undergo a wellcharacterized ring assembly process that will be discussed below (Vavylonis et al 2008). Mid1 likely induces local concentration of contractile ring components, as artificial targeting of several ring components to nodes can largely restore cytokinesis in mid1 mutant cells (Tao et al 2014).…”
Section: Contractile Ring Positioning In Fission Yeastmentioning
confidence: 99%
See 1 more Smart Citation